Methodological strategies for the empowerment of the doctoral student - Ferreira, Jorge; Valduga, Tatiane (Cuadernos de Trabajo Social, 2021)
A long, slow and solitary process characterizes a doctoral thesis that is often interrupted by external and/ or internal factors, leading to a sharp reduction in the number of students attending the training program or a late completion of the process. In this article, we present a set of innovative methodological strategies in the promotion of the Empowerment of the Third Cycle Student (PhD). Strategies ranging from the promotion of integrative student motivational spaces; stimulation of informal student initiative research groups in the realization of online opportunities for establishing contact relationships with other research centers and other students / researchers and creation of field research activities, with the ultimate goal of successful completion of a PhD thesis. In this set of strategies, we include promoting the participation of PhD students in international and national scientific events, as well as encouraging publication in indexed and non-indexed journals and the presentation of Working Papers. As an empirical example, NUDLA / ISCTE - IUL will be presented
Keywords: Tesis doctoral; Estrategias; Metodologías; innovación